Evaluation of blended learning in mathematics courses in the informatics engineering department - Jemakmun; Negara, Edi Surya; Roni, Mukran (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2026)
Mathematics instruction in higher education is increasingly delivered through offline, online, and blended modalities, each characterized by distinct assessment practices. However, the heterogeneity of these instructional arrangements often results in inconsistent learning outcomes and poses challenges for valid measurement of student performance. This study examines the interaction between learning modality—specifically blended learning—and assessment type on students’ mathematics achievement, while explicitly controlling for initial mathematical ability. A quasi-experimental design employing a three-way analysis of variance (ANOVA) was conducted with first-year Informatics Engineering students at Universitas Bina Darma, Indonesia. Descriptive statistics (minimum, maximum, mean, median, mode, variance, and standard deviation) were computed to summarize the data, followed by inferential analyses testing main, interaction, and simple effects. The results revealed a significant interaction effect between blended learning and assessment type, moderated by students’ initial mathematical ability. Students with high prior mathematical ability achieved superior outcomes when participating in blended learning combined with online assessment compared to offline assessment. Similarly, students with low prior mathematical ability demonstrated better performance under online assessment conditions than in offline contexts. Overall, these findings indicate that the integration of online assessment within blended learning environments can enhance student engagement and mathematics achievement across varying ability levels. The results carry important implications for the instructional design and assessment strategies employed in university-level mathematics education.